Comparative test of yield and quality of the fruit Butternut squash (Cucurbita moschata) type in the EEA Anguil of the pampean semiarid region (Semiárida, 2020)
The objective of this work was to evaluate the agronomical performance of seven "Anco" pumpkin cultivars in the semiarid region of La Pampa. A comparative yield and fruit quality experiment was carried out at EEA INTA Anguil during the growing season of 2008. AII crops were planted on 25/11/08 and harvest of all materials took place on 17/03/09. Seven different cultivars were tested: Saxo (Basso), Experimental bushy material (INTA), Experimental material (INTA), Coco (Basso), Atlas (Sakata), Cuyano INTA and Waltham Butternut (Seminis). The experimental design was a randomized block with 4 replications. Each plot included 10 plants separated by 1 m and 2 m between rows. Statistical analysis using ANOVA and Scott & Knott test were performed on the data. Saxo and Atlas cultivars showed a significant total and commercial yields. In commercial yield besides the mentioned, the Material Experimental lNTA stood up. The Material Experimental lNTA showed a smaller percentage of waste, together with Cuyano INTA. Atlas showed a greater fruit size, reaching an average weight of 2.75 kg. Atlas and Waltham Butternut showed a cylindrical form of fruit, while the rest of the materials were piriform.
Keywords: yield components; fruit qualitative analysis; waste percentage; cultivars